Metabolic engineering for the production of isoprene and isopentenol by Escherichia coli - Li, Meijie (Appl Microbiol Biotechnol, 2018)
The biotechnological production of isoprene and isopentenol has recently been studied. Isoprene, which is currently made mainly from petroleum, is an important platform chemical for synthesizing pesticides, medicines, oil additives, fragrances, and more and is especially important in the rubber production industry. Isopentenols, which have better combustion properties than well-known biofuels (ethanol), have recently received more attention. Supplies of petroleum, the conventional source of isoprene and isopentenols, are unsustainable, and chemical synthesis processes could cause serious environmental problems. As an alternative, the biosynthesis of isoprene and isopentenols in cell factories is more sustainable and environmentally friendly. With a number of advantages over other microorganisms, Escherichia coli is considered to be a powerful workhorse organism for producing these compounds. This review will highlight the recent advances in metabolic engineering for isoprene and isopentenol production, especially using E. coli cell factories.